Profile and Areal Surface Characterization of Additive Manufacturing Polymer and Metal Parts - Sagbas, Binnur; Durakbasa, Numan M. (SPRINGER-VERLAG BERLIN, 2019)
Additive manufacturing (AM) has great potential on manufacturing both polymer and metal parts as final product. However, optimization of surface texture quality has not been fully achieved yet. AM surfaces present variable textures that differs according to the AM methods and process parameters. Because of their unusual texture, it is important to evaluate surface properties of metal and polymer parts produced by different AM processes. In this study, it is aimed to define 2D and 3D surface texture of poly-lactic acid (PLA) polymer and AlSi10Mg metal parts manufactured by Fused Deposition Modelling (FDM) and Direct Metal Laser Sintering (DMLS) respectively. ISO 4287 Ra, Rq and Rz profile roughness parameters were defined by tactile method while ISO 25178 Sa, Sq and Sz areal parameters were measured by optical method. Measurements were taken from up-skin and down-skin of the samples which were in 30 mm diameter and 4 mm thickness. Results were evaluated within themselves and literature studies. Differences between profile and areal surface characterization and need of new specifications were also discussed.
Keywords: Surface metrology; Additive manufacturing; FDM; DMLS; TOPOGRAPHY; Engineering